Mental toughness and choking susceptibility in athletes - Thiessen, Burgandy; Blacker, Mishka; Sullivan, Philip (Frontiers in Psychology, 2024)
Choking susceptibility refers to the propensity of an athlete to choke under pressure. There Mesagno (2006) has operationalized choking susceptibility as a combination of scores on selfconsciousness, anxiety and coping. is an operational definition of choking susceptibility comprising relative scores on self-consciousness, anxiety, and coping strategies (Mesagno, 2006). Despite the potential of Mesagno'sthis protocol, there is currently limited support for its validity. Secondly, although mental toughness (MT) has a relationship with sport performance, there is limited research on mental toughness'it's MT's relationship to choking under pressure, specifically. The current study investigateds the relationship between choking susceptibility and mental toughness. in a sample of athletes ranging in experience from recreational to international levels of competition. to provide support for the concurrent validity for Mesagno operational definition. It is was hypothesized that choking susceptible athletes will have significantly lower levels of mental toughness than those who are not choking susceptible. Data from a heterogeneous sample of competitive athletes (N=415) was obtained through a Qualtrics research panel. Results of a Mann-Whitney U Our analyses showed that self-reported mental toughness is was not significantly different in athletes categorized as choking susceptible and non-choking susceptible. etes who were and, sed. CFurtherorrelational analysesresults also highlightshotw specific differences between mental toughness and the composite items scores of choking susceptibility , andwhich provide researchers with avenues for future research in this area alongside a need for each construct to be examined in relation to choking beahviourbehaviour in sport.